Raman scattering effect in atmospheres of giant planets of the Solar System from high-resolution spectral data - Kuznyetsova, Yu.G.; Vid'machenko, A.P. (Кинематика и физика небесных тел, 2005)
Some results of study for high-resolution spectra of Jupiter and Saturn atmospheres are presented. The spectral data are derived with the help of the coude echelle spectrometer installed on the 2-m telescope at the Terskol Observatory (the Northern Caucasus). The investigations are carried out with consideration for Raman light scattering. Calculations for molecular scattering effect in the atmospheres of giant planets are made for visible part of the spectrum. Wavelengths of Fraunhofer lines and their strongest ghosts caused by the rotational S(0), S(1), O(2) and the vibrational Q₁(1) transitions are used.